Dynamic Contract Trading in Spectrum Markets - Kasbekar, G. S.; Sarkar, S.; Kar, K.; Muthuswamy, P. K.; Gupta, A. (IEEE transactions on automatic control, 2014)
We propose a structured spectrum market and consider two basic types of spectrum contracts that can help attain desired flexibilities and trade-offs in terms of service quality, spectrum usage efficiency and pricing: long-term guaranteed-bandwidth contracts, and short-term opportunistic-access contracts. A primary provider (seller) and a secondary provider (buyer) creates and maintains a portfolio composed of an appropriate mix of these two types of contracts. We address the question of how the spectrum contract portfolio of a seller (buyer) in the spectrum market should be dynamically adjusted, so as to maximize return (minimize cost) subject to meeting the bandwidth demands of its own subscribers. We formulate the above question as a stochastic dynamic programming problem, and obtain structural properties of the optimal dynamic trading strategy that takes into account the current market prices of the contracts and the subscriber demand process in the decision-making.